Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1073/pnas.1219808110
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of MC4R to agonist in the endoplasmic reticulum stabilizes an active conformation of the receptor that does not desensitize

Abstract: Melanocortin-4 receptor (MC4R) is a G protein-coupled receptor expressed in neurons of the hypothalamus where it regulates food intake. MC4R responds to an agonist, α-melanocyte-stimulating hormone (α-MSH) and to an antagonist/inverse agonist, agoutirelated peptide (AgRP), which are released by upstream neurons. Binding to α-MSH leads to stimulation of receptor activity and suppression of food intake, whereas AgRP has opposite effects. MC4R cycles constantly between the plasma membrane and endosomes and underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…One of the variants tested in the present study, V50M, did exhibit a defect in glycosylation, reduced responsiveness to α‐ and β‐MSH, and reduced the ability to couple to β‐arrestin, although it is unclear whether the glycosylation defect contributes to the altered signalling properties. Granell et al suggest that glycosylation status may not affect the function of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…One of the variants tested in the present study, V50M, did exhibit a defect in glycosylation, reduced responsiveness to α‐ and β‐MSH, and reduced the ability to couple to β‐arrestin, although it is unclear whether the glycosylation defect contributes to the altered signalling properties. Granell et al suggest that glycosylation status may not affect the function of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Changing conformation of newly synthesized MC4R along the secretory pathway may also affect the receptor properties not only to signal, but also to desensitize. In this respect, co-expressing α-MSH together with MC4R in the ER can rescue an obesitylinked variant retained in the ER and stabilize the wildtype receptor in an active conformation that does not route to lysosomes nor desensitizes (Granell et al 2013). These observations indicate that MC4R conformation and ability to signal can be modulated by interactions with agonist in the ER.…”
Section: Pharmacological Chaperones and Folding Of Mc4rmentioning
confidence: 90%
“…Studies based on undifferentiated cells, neuronal cells and immortalized hypothalamic cells indicate that desensitization of MC4R takes place by a process where, upon prolonged agonist exposure, the receptor routes to the lysosomes, instead of being made available at the cell membrane (Gao et al 2003, Shinyama et al 2003, Mohammad et al 2007, Granell et al 2013. MC4R is internalized at the same rate in the presence or absence of α-MSH agonist (Mohammad et al 2007).…”
Section: Intracellular Traffic Of Mc4r and Response To Melanocortin Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been performed to correct the localization of misfolded MC4Rs through modulating molecular chaperone such as heat shock cognate protein 70 6, or using chemical chaperones such as 4-phenyl butyric acid 7, or several nonpeptidic MC4R antagonists as pharmacological chaperones (pharmacoperones) 8-11. A more recent study using endoplasmic reticulum-targeted α-MSH showed that it also promotes the cell surface expression of I316S MC4R 12. In these studies, most of the misfolded MC4Rs become functional when corrected to the cell surface.…”
Section: Introductionmentioning
confidence: 99%